Contribution of glutathione S-transferase gene polymorphisms to development of skin cancer - Lei, Zeyuan (Int J Clin Exp Med, 2015)
Background: Glutathione S-transferase (GST) family genes are of vital importance in maintaining cellular defence systems, protecting cells against the toxic effects of reactive oxygen produced during the synthesis of melanin, and detoxifying environmental mutagens and chemical or synthetic drugs. As no previous meta-analyses have examined the association of polymorphisms at GSTT1, GSTP1 Ile105Val with skin cancer risk and independently published studies have produced inconsistent conclusions, we were promoted to estimate the associations in the largest study to date. Methods: Computer-assisted searches were carried out to systematically identify the studies of GST polymorphisms and skin cancer. The eligibility of studies was evaluated following the requirements of inclusion criteria. Risk of skin cancers (OR and 95% CI) was assessed with the fixed or random effects meta-analysis. Major findings: The fixed effects meta-analysis of 15 studies suggested no overall association between GSTT1 null and skin cancer. Nor was there a significant association in any subgroup. However, in the stratified analysis by histologic type for GSTP1 Ile105Val, we found 1.56 times higher risk of malignant melanoma (MM) among people with the 105-Val/Val genotype (Val/Val vs. Ile/Ile: OR = 1.56, 95% CI = 1.05-2.32, p(heterogeneity) = 0.584). Conclusions: These statistical data demonstrate that Ile105Val polymorphism of the GSTP1 gene may have genetic contribution to the development of skin cancer, MM in particular.